2022
DOI: 10.1021/acsenergylett.2c00780
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivated p-Doping of Organic Interlayer Enables Efficient Perovskite/Silicon Tandem Solar Cells

Abstract: Solution-processed organic semiconductor layers on rough surfaces tend to vary widely in thickness, significantly hindering charge extraction in relevant optoelectronic devices. Herein, we report the photoactivated p-doping of hole-transporting material (HTM) to enhance hole extraction for (textured) perovskite/silicon tandem solar cells, making the device performance less sensitive to the variation of hole transport layer thickness. We used the ionic compound 4isopropyl-4′-methyldiphenyliodonium tetrakis(pent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The elevated hole mobility is due to the oxidation of the triphenylamine moiety by hydrogen tetrakis(pentafluorophenyl)borate, thus generating cationic radicals. 15,35,36 The mechanism for the generation of hydrogen tetrakis(pentafluorophenyl)borate is described in Fig. S22 (ESI†).…”
Section: Resultsmentioning
confidence: 99%
“…The elevated hole mobility is due to the oxidation of the triphenylamine moiety by hydrogen tetrakis(pentafluorophenyl)borate, thus generating cationic radicals. 15,35,36 The mechanism for the generation of hydrogen tetrakis(pentafluorophenyl)borate is described in Fig. S22 (ESI†).…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers would like to improve the conductivity of PTAA by doping with small molecules like F4-TCNQ. Zheng et al reported the p-doping of PTAA to facilitate hole extraction for 2-T perovskite/ silicon TSCs, making the device performance less sensitive to the thickness of PTAA [177]. The p-doping with ionic compound 4-isopropyl-4'-methyldiphenyliodonium tetrakis(penta-fluorophenyl-borate) (DPI-TPFB) dopant is activated by light-soaking treatment, resulting in nearly 22 times higher conductivity than that of pristine PTAA.…”
Section: Compared With P-i-n Pscs the Superior Energy Level Alignment...mentioning
confidence: 99%
“…As the most promising method to approach the S-Q limit efficiency of perovskites, TSCs will also make great contribution to promoting the commercial application of ST-PSCs. [172,173]…”
Section: Application Of St-pscs On Tandem Solar Cellsmentioning
confidence: 99%